The analysis of teacher digital pedagogical competencies in facing technological development in learning - Bentri, Alwen; Hidayati, Abna; Saputra, Andra; Arina, Novra (Jurnal Cakrawala Pendidikan, 2025)
Digital pedagogical competency is crucial for teachers in today’s digital age, enabling them to harness technology effectively in the learning process. This research aims to analyze the factors that influence digital pedagogy competence among elementary school teachers. The factors studied involve Content Knowledge (CK), Pedagogical Knowledge (PK), Technology Knowledge (TK), Technological Content Knowledge (TCK), Technological Pedagogical Knowledge (TPK), Pedagogical Content Knowledge (PCK), and Technological Pedagogical Content Knowledge (TPACK). The research employed a quantitative survey approach with regression analysis through the use of questionnaires to teachers as respondents. The research results show that teachers demonstrate strengths across several indicators, such as Content Knowledge (CK) of 80.89%, Pedagogical Knowledge (PK) of 79.11%, and Technology Knowledge (TK) of 82.89%, Technological Content Knowledge (TCK) of 84.52 % and Technological Pedagogical Knowledge (TPK) of 85.11%. The Pedagogical Content Knowledge (PCK) indicator reached 83.04%, while that of the Technological Pedagogical Content Knowledge (TPACK) was 84.44%. The findings of this research provide an in-depth understanding of the state of digital competence among elementary school teachers. Identifying teacher successes and highlighting gaps that need further attention is an important part of this research. Apart from that, this research also discusses the impact of teachers' digital pedagogy competencies on student learning outcomes and their preparation for facing the digital era. This research constitutes a significant contribution to understanding and improving teachers' digital pedagogy competencies to support optimizing technology in the learning process in the current digital era.